Effect of Green Human Resource Management and Green Leadership On Employee Performance at PERUMDA Tirta Mangkaluku, Palopo City - Ariska Putri Mase; Muhammad Kasran; I Ketut Patra (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This study aims to determine the effect of Green Human Resource Management and Green Leadership on employee performance at Perumda Tirta Mangkaluku, Palopo City. Methodology: This study uses a quantitative method, with a population of 316 employees and a sampling technique using the Slovin formula totaling 76 people and using the Simple Random Sampling technique. To collect data, a questionnaire with a Likert scale was used. Data analysis used multiple linear regression techniques with the help of SPSS software version 26. Results: The research shows that: (1) Green Human Resource Management has a significant influence on employee performance, (2) Green Leadership does not have a significant influence on employee performance, and (3) both variables, namely Green Human Resource Management and Green Leadership, together have a significant influence on employee performance. Findings: The findings confirm that GHRM is a key driver of performance, while Green Leadership alone does not significantly affect performance outcomes. Novelty & Originality: This study offers novelty by examining GHRM and Green Leadership in a regional water utility company in Palopo, a context rarely explored in prior research. Conclusions: This research shows that companies need to improve environmentally based human resource management practices to improve employee performance. Type of Paper: This paper is an empirical research paper.